2016
DOI: 10.1002/bdrb.21189
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity studies of lumefantrine and artemether in rats and rabbits

Abstract: The combination of artemether plus lumefantrine is a type of artemisinin-based combination therapy (ACT) recommended by the World Health Organization for uncomplicated falciparum malaria except in the first trimester of pregnancy. The first trimester restriction was based on the marked embryotoxicity in animals (including embryo death and cardiac and skeletal malformations) of artemisinins such as artesunate, dihydroartemisinin, and artemether. Before recommending ACTs for use in the first trimester, the World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is an unusual feature of thalidomide that it caused high incidences of unusual malformations at nonmaternally toxic doses in rabbits and primates (e.g., Christian et al, ). Artesunate, artemether, and DHA have also caused embryo deaths and/or malformations at nonmaternally toxic doses when tested in rats, rabbits, and/or monkeys (Clark et al, , , ).…”
Section: Developmental Toxicity Studies In Animals and Their Interprementioning
confidence: 99%
See 2 more Smart Citations
“…It is an unusual feature of thalidomide that it caused high incidences of unusual malformations at nonmaternally toxic doses in rabbits and primates (e.g., Christian et al, ). Artesunate, artemether, and DHA have also caused embryo deaths and/or malformations at nonmaternally toxic doses when tested in rats, rabbits, and/or monkeys (Clark et al, , , ).…”
Section: Developmental Toxicity Studies In Animals and Their Interprementioning
confidence: 99%
“…In the second pharmacokinetic study (Tarning et al, ), blood sampling started at the first dose and extended to 168 hr after the last dose. The C max and AUC 48‐72h values for lumefantrine were estimated to be 9.2 μg/ml and 170 μg.h/ml, respectively (Clark et al, ).…”
Section: Lumefantrinementioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that artesunate caused embryo-lethality at doses ≥12 mg/kg/day administered for more than 12 days at the beginning of organogenesis, but not when administered for shorter treatment period [ 53 ]. It is interesting to note that although ACT and not artemisinin monotherapy, is the recommended treatment against uncomplicated malaria, the developmental toxicity of ACTs, compared to artemisinin derivatives alone, has been scarcely studied in vitro [ 54 , 55 ].…”
Section: Developmental Toxicity Data Of Artemisinin Derivativesmentioning
confidence: 99%
“…In the rat EFD study of artemether (Clark, Youreneff, & DeLise, 2016), there was no maternal toxicity at any dose tested (1, 3, and 10 mg/kg/day) but developmental effects seen at the high dose consisted of 16 total litter resorptions among 25 pregnant females, increased early resorptions in the remaining litters, a 13% decrease in mean fetal weight, and an increased incidence of fetuses with wavy/angulated rib (Clark et al, 2016). The middle dose group (3 mg/kg/day) was the dNOEL.…”
Section: Studies In Rats and Rabbits Conducted After 1995mentioning
confidence: 99%